Training and Training Based on Field Training Model (Internship) - Rivendri, Rivendri (Universitas Negeri Padang, 2023)
Internship is training or practice to master certain skills under the guidance and supervision of experienced instructors. Apprenticeship training is organised and directed to equip, improve, and develop work competencies in order to improve capability, productivity, and welfare. The learning concept of apprenticeship is student-centred, prioritising the activities of learners as apprentices through active student learning and providing opportunities for learners to self-direct their learning activities. The benefits obtained in the implementation of apprenticeship are not only felt by the company that can produce labour in accordance with industry standards and company needs, but also the apprentices themselves get the opportunity to receive training, not only to hone skills in accordance with industry / company standards, but also to get direct technical training and core work skills that can improve their performance. The conceptual model underlying the apprenticeship programme falls into the category of the implementative learning model. Where this model requires initiatives that are able to strive and realise the curriculum from potential or written to actual or realisation by conducting a series of implementation activities in the form of learning processes.